Catalytic Glucose Isomerization by Porous Coordination Polymers with Open Metal Sites. Issue 10 (30th July 2014) - Akiyama, George; Matsuda, Ryotaro; Sato, Hiroshi; Kitagawa, Susumu
Abstract Highly efficient catalytic isomerization reactions from glucose to fructose in aqueous media using porous coordination polymers (PCPs) or metal–organic frameworks (MOFs) is reported for the first time. The catalytic activity of PCPs functionalized with NH2, (CH3)2, NO2, and SO3H groups on the pore surface is systematically tested. The catalytic activity can be tuned by the acidity of open metal sites (OMSs) by modifying the organic linkers with the functional groups. As a result, it is demonstrated that MIL‐101 functionalized with SO3H not only shows high conversion of glucose but also selectively produces fructose. Further, catalytic one‐pot conversion of amylose to fructose is achieved, thanks to the high stability of the framework in an acidic solution. These results show that MOF/PCP compounds having OMSs are promising materials for various useful heterogeneous catalytic reactions, in particular in the biomass field.